Russian Federation : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This report on the Russian Federation's Article IV Consultation highlights Data Module and response by the authorities. Russia's statistical system has made good progress in adopting international statistical methodologies in response to the need to capture in the statistics the country's transition to a market economy. These improvements have been achieved notwithstanding the statistical challenges posed by extraordinary economic events during the transition, including the financial crisis of 1998. Appropriate measures are taken in the assessment and validation of source data, intermediate data, and statistical outputs.